Factors Influencing the Achievement of Social Development Goals in Public Universities - Musa, Alshahrani Ahmed; Mohamed, Rosmah; Subramaniam, Anusuiya (Advances in Social Sciences Research Journal, 2024)
Achieving Social Development Goals (SDGs) within public universities is essential for fostering sustainable development globally. Despite the extensive research on sustainability in higher education, significant gaps remain regarding specific factors influencing SDG achievement in public universities. This study addresses these gaps by examining the integration of green human resource management (HRM) practices, green organizational culture, green knowledge sharing, stakeholder engagement, curriculum integration, and infrastructure and policy updates. Utilizing a systematic literature review spanning from 2013 to 2024, this research synthesizes findings from Scopus and Web of Science databases, focusing on open-access articles relevant to the scope of the study. The results reveal that while traditional factors such as adequate funding, education and training, partnerships, and accountability are well-studied, the newer dimensions of green practices and stakeholder involvement are less explored yet critically important. This study underscores the multifaceted nature of sustainability efforts in higher education and advocates for a comprehensive strategy that incorporates both established and innovative practices. By highlighting these underexplored factors, this research provides valuable insights and practical recommendations for public universities to enhance their contribution to sustainable development, ultimately promoting a more sustainable future.